Challenging HIV and AIDS : a new role for Caribbean education; foreword by Sir George Alleyne - Morrisey, Michael (UNESCO ParisFR, 2010)
Chronicles the response of the education sector in the Caribbean in halting the spread of the HIV/AIDS epidemic.